Tinjauan Hukum Islam tentang Sisa Panjar Biaya Perkara yang Daluwarsa di Pengadilan Agama Rengat - Putri Sakinah; Ismail Ismail (Lembaga Yasin AlSys, 2026)
The issue of managing the remaining unclaimed advance court fees by the parties at Pengadilan Agama Rengat gives rise to a normative problem between Indonesian positive law and Islamic law. Under positive law, the remaining advance court fees that are not claimed within six months after notification are deposited into the state treasury as Penerimaan Negara Bukan Pajak, whereas in Islamic law ownership of property cannot be transferred solely due to expiration. This study aims to analyze the mechanism for managing the remaining advance court fees at Pengadilan Agama Rengat and to examine its conformity with the principles of Islamic law. This study used a field research method with a qualitative approach. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data display, and conclusion drawing. The results showed that the management of advance court fees at Pengadilan Agama Rengat had been carried out transparently and accountably in accordance with the provisions of statutory regulations. From the perspective of Islamic law, advance court fees fall under the contract of wadi’ah yad amanah, namely a deposit that must be safeguarded and may not be used other than for the purposes of the judicial process. In principle, the transfer of ownership of the remaining advance fees due to expiration is not in line with the concept of ownership in Islam and is closer to the concept of luqathah. However, through the maslahah mursalah approach, the practice of depositing the remaining advance court fees into the state treasury may be justified because it aims to realize public benefit, maintain orderly judicial administration, and prevent the potential misuse of funds. Thus, the policy may be regarded as consistent with the principles of Islamic law that prioritize benefit and the welfare of the community.